Pemodelan Pola Transport Sedimen di Perairan Desa Berakit dan Pengudang Kabupaten Bintan - Rahma Sarita; Mario Putra Suhana; Harish Wirayuhanto (Universitas Trunojoyo Madura, 2023)
Sedimentation and erosion processes can be influenced by hydro-oceanographic factors. These factors include waves, currents, and tides because they interact directly with the coastal/coastal area. Related to these problems, sedimentation and erosion is one thing that needs to be studied. One way that is used in providing information about these that is widely used is to use a hydrodynamic model. Based on this, it can be seen that it is important to conduct research to determine sediment properties such as the type and type of sediment with sediment transportt modeling in Berakit and Pengudang villages. This research was carried out using the MIKE21 Software hydrodynamic modeling for one month in June 2021 using hydrodynamic modeling, the Flow Model FM Sand Transportt module. Sediment transportt observed is bottom sediment or bed load. The research results are shown in 4 conditions, namely towards high tide, highest tide, towards low tide and lowest tide. Sediment transportt at high tide with erosion of -0.10 and sedimentation of 0.25 m/day and at the highest tide shows an erosion value of -0.24 and sedimentation of 0.32 m/day. Sediment transportt towards low tide with erosion of -0.15 and sedimentation of 0.20 m/day and at the lowest ebb erosion occurs with a value of -0.36 and sedimentation of 0.20 m/day.